On the dense plasma decay within the electron concentration range of 10¹⁷ cm⁻³≤Ne≤10²² cm⁻³ - Fedorovich, О.А.; Voitenko, L.M. (Вопросы атомной науки и техники, 2013)
The paper presents the results of comparison between the experimental decay coefficients of the dense plasma produced by pulsed discharges in water with theoretical coefficients calculated using all the known formulas for the three-particle recombination with the plasma ionization taken into account. The best agreement was obtained in the calculations of the ternary recombination with taking into account only the levels realized in the dense plasma and with taking into account the ionization using the experimental decay coefficients of the dense plasma. Наведено результати порівняння експериментальних коефіцієнтів розпаду густої плазми імпульсних розрядів у воді з теоретичними коефіцієнтами, розрахованими за всіма відомими формулами для тричасткової рекомбінації з урахуванням іонізації плазми. Найкращу згоду з експериментальними коефіцієнтами розпаду густої плазми отримано при розрахунку коефіцієнтів потрійної рекомбінації з урахуванням тільки тих рівнів, які реалізувалися в щільній плазмі із урахуванням іонізації. Приведены результаты сравнения экспериментальных коэффициентов распада плотной плазмы импульсных разрядов в воде с теоретическими, рассчитанными по всем известным формулам коэффициентами для трехчастичной рекомбинации с учетом ионизации плазмы. Наилучшее согласие получено при расчете коэффициентов тройной рекомбинации с учетом только реализовавшихся в плотной плазме уровней и учетом ионизации с экспериментальными коэффициентами распада плотной плазмы.